Respuesta :

[tex](-2a^4b) \times (5a^4b^3) = -10a^{4+4}b^{1+3} = -10a^8b^4[/tex]

Answer:

Simplification of [tex](-2a^4b)(5a^4b^3)[/tex] is:

[tex]-10a^8b^4[/tex]

Step-by-step explanation:

We have to simplify:

[tex](-2a^4b)(5a^4b^3)[/tex]

On combining the like terms, we get

[tex]-2\times 5\times a^4\times a^4\times b\times b^3[/tex]

= [tex]-10\times a^{4+4}\times b^{1+3}[/tex]

= [tex]-10a^8b^4[/tex]

Hence, simplification of [tex](-2a^4b)(5a^4b^3)[/tex] is:

[tex]-10a^8b^4[/tex]

ACCESS MORE